Sleep Disturbances in Chronic Pain: Neurobiology, Assessment, and Treatment in Physical Therapist Practice. Issue 5 (7th February 2018) - Nijs, Jo; Mairesse, Olivier; Neu, Daniel; Leysen, Laurence; Danneels, Lieven; Cagnie, Barbara; Meeus, Mira; Moens, Maarten; Ickmans, Kelly; Goubert, Dorien
Abstract: Among people with chronic pain, insomnia is highly prevalent, closely related to the mechanism of central sensitization, characterized by low-grade neuroinflammation, and commonly associated with stress or anxiety; in addition, it often does not respond effectively to drug treatments. This review article applies the current understanding of insomnia to clinical practice, including assessment and conservative treatment of insomnia in people with chronic pain. Cognitive-behavioral therapy for insomnia can be efficacious for improvements in sleep initiation, sleep maintenance, perceived sleep quality, and pain interference with daily functioning in people with chronic pain. A recent systematic review concluded that with additional training, physical therapist–led cognitive-behavioral interventions are efficacious for low back pain, allowing their implementation within the field. Cognitive-behavioral therapy for insomnia, as provided to people with chronic pain, typically includes education, sleep restriction measures, stimulus control instructions, sleep hygiene, and cognitive therapy.